Decision modeling in donation after circulatory death liver transplantation. Issue 5 (May 2017) - McLean, Kenneth A.; Camilleri‐Brennan, Julian; Knight, Stephen R.; Drake, Thomas M.; Ots, Riinu; Shaw, Catherine A.; Wigmore, Stephen J.; Harrison, Ewen M.
Abstract : Donation after circulatory death (DCD) liver allografts are increasingly used for transplantation. However, the posttransplantation clinical and quality of life outcomes of DCD recipients are traditionally considered to be inferior compared with donation after brain death (DBD) allograft recipients. Decision making for such marginal organs can be difficult. This study investigated the optimal decision to accept or decline a DCD liver allograft for a patient based on their current health. A Markov decision process model was constructed to predict the 5‐year clinical course of patients on the liver transplant waiting list. Clinical outcomes were determined from the UK transplant registry or appropriate literature. Quality‐adjusted life years (QALYs) were determined using the condition‐specific short form of liver disease quality of life (SF‐LDQoL) questionnaire. There were 293/374 (78.3%) eligible patients who completed the SF‐LDQoL questionnaire. A total of 73 respondents (24.9%) were before transplant and 220 were after transplant (DBD recipient, 56.3%; DCD recipient, 8.5%; ischemic cholangiopathy patient, 2.4%; retransplant recipient, 7.9%). Predictive modeling indicated that QALYs gained at 5 years were significantly higher in DCD recipients (3.77; 95% confidence interval [CI], 3.44‐4.10) compared with those who remained on the waiting list for a DBD transplant with Model for End‐Stage Liver Disease (MELD) scores of 15‐20 (3.36; 95% CI, 3.28‐3.43), or >20 (3.07; 95% CI, 3.00‐3.14). There was no significant advantage for individuals with MELD scores <15 (3.55; 95% CI, 3.47‐3.63). In conclusion, this model predicts that patients on the UK liver transplant waiting list with MELD scores >15 should receive an offered DCD allograft based on the QALYs gained at 5 years. This analysis only accounts for donor‐recipient risk pairings seen in current practice. The optimal decision for patients with MELD scores <15 remains unclear. However, a survival benefit was observed when a DCD organ was accepted. Liver Transplantation 23 594–603 2017 AASLD .